Congenic mapping and genotyping of the tetrahydrobiopterin-deficient hph-1 mouse. - Khoo, J; Nicoli, T; Alp, N; Fullerton, J; Flint, J; Channon, K (2004)
The hph-1 ENU-mutant mouse provides a model of tetrahydrobiopterin deficiency for studying hyperphenylalaninaemia, dopa-response dystonia, and vascular dysfunction. We have successively localized the hph-1 mutation to a congenic interval of 1.6-2.8 Mb, containing the GCH gene encoding GTP cyclohydrolase I (GTP-CH I). We used these data to establish a PCR method for genotyping wild type, hph-1 and heterozygote mice, and found that heterozygote animals have partial tetrahydrobiopterin deficiency. These new findings will extend the utility of the hph-1 mouse in studies of GTP-CH I deficiency.